Investigation on the growth and luminescence spectra of congruent Linbo3 crystal obtained in air atmosphere by Czochralski Method - H. K., Hamdan; D. P., Ngurah Made; Sudin, M. Radzi; Saidin, M. Khairi; Rohani, Md. Supar (Faculty of Science, UTM, 2008)

(untitled)
Single crystal of Congruent LiNbO3 (CLN) was grown by the Czochralski method in an air atmosphere with ADC (Automatic Diameter Control) r.f. heating. In this study, the optimum conditions required to grow high quality CLN single crystal are described. The high quality CLN single crystal with growth direction of ?001? was produced by effective control of growth conditions. The luminescence spectra from LiNbO3 is due to change?transfer in the niobate octahedron, and is strongly affected by the concentration of Li vacancies. For CLN single crystal at room temperature under 300nm wavelength excitation, the emission maximum is 760 nm. There are significant differences between the intensity of component emission band in the X, Y and Z cut crystals. Luminescence decay times and intensity variations gives a qualitative measure of both purity and crystal quality.